2014
DOI: 10.1002/berj.3135
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and education: comparing the national curricula of the states of the European Union and the United Kingdom

Abstract: In the past 20 years the importance of creativity as part of young people's education has increasingly been recognised. The stimulus for the growing emphasis on creativity has come from diverse sources including drives for greater national economic prosperity and enlightenment visions of young people's education. One facet of creativity in education has been its place in the national curriculum texts of nation states. The research reported in this paper aimed to investigate the place of creativity in the natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 26 publications
0
56
0
4
Order By: Relevance
“…The interest in human creativity seems to have not led to either substantial advances in the understanding of creative processes nor to theory-based techniques for enhancing human creativity. Even if in the past 20 years the relevance of creativity emerged as a need to improve students' curricula (Wyse & Ferrari, 2015), in the Italian schooling system there are no standard defined techniques or methods teachers normally use to assess student skills and talents.…”
Section: Creativity As a Learning Objectivementioning
confidence: 99%
“…The interest in human creativity seems to have not led to either substantial advances in the understanding of creative processes nor to theory-based techniques for enhancing human creativity. Even if in the past 20 years the relevance of creativity emerged as a need to improve students' curricula (Wyse & Ferrari, 2015), in the Italian schooling system there are no standard defined techniques or methods teachers normally use to assess student skills and talents.…”
Section: Creativity As a Learning Objectivementioning
confidence: 99%
“…These scientists applied their scientific and technological expertise and creativity to develop an air-filled pneumatic tyre, waterproof fabric and improved road construction, respectively. Wyse and Ferrari (2015) also emphasised the disparity between disciplines when they found that all current UK curriculum texts refer to creativity twice as much in the arts documentation as in other subject areas. This resonates with Robinson's (2009) belief that previous (and current) governments have not and do not appear to value, promote and explicitly support creativity within disciplines such as the sciences.…”
Section: Mcgregor and S Frodshammentioning
confidence: 99%
“…Similarly, other researchers have highlighted the importance of novelty as well as desired utility, appropriateness or value to the field within which it is applied to (Beghetto, 2005;Runco and Jaeger, 2012;Shah et al, 2003;Sternberg and Lubart, 1999;Wyse and Ferrari, 2015). Some definitions additionally include that the idea should be non-obvious or surprising in some way (Crilly and Cardoso, 2017;Howard et al, 2008).…”
Section: Pd Creativity and Design Examplesmentioning
confidence: 99%